Effects of oleic acid on the tissue factor activity, blood lipids, antioxidant and oxidant parameters of streptozotocin induced diabetic rats fed a high-cholesterol diet - YARAT, AYŞEN (SPRINGER BIRKHAUSER, 2010)
Ecological studies have suggested an inverse association between monounsaturated fat intake and total mortality, as well as with coronary heart diseases death. Whether the beneficial effects of olive oil on the cardiovascular system are exclusively due to oleic acid remains to be elucidated. The aim of this study was to investigate the effects of oleic acid consumption for three months on lipid profile, oxidant-antioxidant status and tissue factor (TF) activities in streptozotocin (STZ) induced diabetic rats fed a high-cholesterol diet. Forty rats were divided into 5 groups of 8 rats each as control (C), STZ induced diabetic controls (DC); high-cholesterol fed hyperlipidemic controls (HC); diabetic rats fed a high cholesterol diet (Diabetic-Hyperlipidemic, DH) and diabetic-hyperlipidemic + oleic acid (DHO) group. Blood samples were used to evaluate lipid profile, hemostatic parameters, glutathione (GSH), thiobarbituric acid reactive substances (TBARS); tissue samples were used for the determination of TF activities. Oleic acid consumption beneficially affected serum total lipid, triacylglycerol and GSH levels and decreased TF activities of brain and kidney in DHO group compared with the DH group. Oleic acid may have protective effects against cardiovascular complications of diabetes since GSH, total lipid and TG levels were beneficially affected. The decreased TF activity in DHO group may protect these tissues from the risk of thrombosis. Nevertheless, further studies are needed to determine the mechanisms that lead to the changes in the TF activity of tissues due to oleic acid consumption.
Keywords: Oleic acid; Tissue factor; Diabetes; Hyperlipidemia; OXIDATIVE STRESS; OLIVE OIL; SERUM-LIPIDS; GLUTATHIONE; INFLAMMATION; FAT